Long-term outcomes of survivors with influenza A H1N1 virus-induced severe pneumonia and ARDS: a single-center prospective cohort study - Tang, Xiao; Xu, Xiao-Li; Wan, Na; Zhao, Yu; Wang, Rui; Li, Xu-Yan; Li, Ying; Wang, Li; Li, Hai-Chao; Gu, Yue; Zhang, Chun-Yan; Yang, Qi; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Systematic evaluation of long-term outcomes in survivors of H1N1 is still lacking. This study aimed to characterize long-term outcomes of severe H1N1-induced pneumonia and acute respiratory distress syndrome (ARDS). This was a single-center, prospective, cohort study. Survivors were followed up for four times after discharge from intensive care unit (ICU) by lung high-resolution computed tomography (HRCT), pulmonary function assessment, 6-minute walk test (6MWT), and SF-36 instrument. A total of 60 survivors of H1N1-induced pneumonia and ARDS were followed up for four times. The carbon monoxide at single breath (DLCO) of predicted values and the 6MWT results didn’t continue improving after 3 months. Health-related quality of life didn’t change during the 12 months after ICU discharge. Reticulation or interlobular septal thickening on HRCT did not begin to improve significantly until the 12-month follow-up. The DLCO of predicted values showed negative correlation with the severity degree of primary disease and reticulation or interlobular septal thickening, and a positive correlation with physical functioning. The DLCO of predicted values and reticulation or interlobular septal thickening both correlated with the highest tidal volume during mechanical ventilation. Levels of fibrogenic cytokines had a positive correlation with reticulation or interlobular septal thickening. The improvements in pulmonary function and exercise capacity, imaging, and health-related quality of life had different time phase and impact on each other during 12 months of follow-up. Long-term outcomes of pulmonary fibrosis might be related to the lung injury and excessive lung fibroproliferation at the early stage during ICU admission.